Photocatalytic oxidation of waste cooking oil using zeolite ZSM-5 & TiO2 as catalyst: a parametric optimization study via response surface methodology / Diyana Natasha Darimi and Siti Khatijah Jamaludin - Darimi, Diyana Natasha; Jamaludin, Siti Khatijah (2020)
Waste cooking oil (WCO) are generated large scale all over the world, hence it has devised serious problems of its waste management which contributes to water pollution. There are variety of methods in order to treat WCO, which are by esterification, transesterification, recycle process and photocatalytic oxidation (PCO) technology process. Among all these three processes, PCO is the least applied for water treatment. It is because this process needs to use of catalyst in order to have high reactive of PCO reaction. This review study explores the PCO process using zeolite ZSM-5 and TiO2 as catalyst. The aim of this study is to review on characterization of WCO and catalyst (TiO2 and ZSM-5). Other than that, the main aim of this study is to review the optimization of reaction conditions such as pH of solution, reaction temperature, catalyst loading and type of catalyst used (TiO2, ZSM-5) on the removal of WCO by using Response Surface Methodology (RSM). The review study presented here are based on literatures from year 2015 until present which were retrieved from databases such as Scopus, Research Gate and Science Direct. The results showed that, harmful organic molecules such as Free Fatty Acid (FFA) are contained in WCO as reviewed from Fourier-Transform Infrared Spectroscopy (FTIR) results. Brunauer-Emmett-Teller (BET) and Thermal Gravimetric Analysis (TGA) reviewed that ZSM-5 has high surface area and thermal stability which comparable to TiO2 and other catalyst (Pt and Ag). The reviewed of various optimization studies via RSM shows that the optimum parameters are pH of solution (6-7), reaction temperature (30°C-50°C), catalyst dosage (0.1 g 100mL-1-0.3 g 100mL-1) and type of catalyst used (ZSM-5). In addition, some researcher proved that other factors such as light intensity and irradiation time are also important in PCO to treated WCO.